Religious dress in the jurisprudence of the European Court of Human Rights - Fernández Codina, Gonzalo (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2025)
The objective of this text is to critically analyze the jurisprudence of the ECtHR on art. 9 ECHR in relation to the use of religious clothing and symbols in order to demonstrate their erratic and incoherent nature and, in general, the many doubts suggested by the various arguments used over the years.